OATP1B1-related drug–drug and drug–gene interactions as potential risk factors for cerivastatin-induced rhabdomyolysis - Tamraz, Bani (2013)
OBJECTIVE: Genetic variation in drug metabolizing enzymes and membrane transporters as well as concomitant drug therapy can modulate the beneficial and the deleterious effects of drugs. We investigated whether patients exhibiting rhabdomyolysis who were taking cerivastatin possess functional genetic variants in SLCO1B1 and whether they were on concomitant medications that inhibit OATP1B1, resulting in accumulation of cerivastatin. METHODS: This study had three components: (a) resequencing the SLCO1B1 gene in 122 patients who developed rhabdomyolysis while on cerivastatin; (b) functional evaluation of the identified SLCO1B1 nonsynonymous variants and haplotypes in in-vitro HEK293/FRT cells stably transfected with pcDNA5/FRT empty vector, SLCO1B1 reference, variants, and haplotypes; and (c) in-vitro screening of 15 drugs commonly used among the rhabdomyolysis cases for inhibition of OATP1B1-mediated uptake of cerivastatin in HEK293/FRT cells stably transfected with reference SLCO1B1. RESULTS: The resequencing of the SLCO1B1 gene identified 54 variants. In-vitro functional analysis of SLCO1B1 nonsynonymous variants and haplotypes showed that the V174A, R57Q, and P155T variants, a novel frameshift insertion, OATP1B1*14 and OATP1B1*15 haplotype were associated with a significant reduction (P<0.001) in cerivastatin uptake (32, 18, 72, 3.4, 2.1 and 5.7% of reference, respectively). Furthermore, clopidogrel and seven other drugs were shown to inhibit OATP1B1-mediated uptake of cerivastatin. CONCLUSION: Reduced function of OATP1B1 related to genetic variation and drug–drug interactions likely contributed to cerivastatin-induced rhabdomyolysis. Although cerivastatin is no longer in clinical use, these findings may translate to related statins and other substrates of OATP1B1.